Loss of RASGRP1 in humans impairs T‐cell expansion leading to Epstein‐Barr virus susceptibility. Issue 2 (8th January 2018) - Winter, Sarah; Martin, Emmanuel; Boutboul, David; Lenoir, Christelle; Boudjemaa, Sabah; Petit, Arnaud; Picard, Capucine; Fischer, Alain; Leverger, Guy; Latour, Sylvain
Abstract: Inherited CTPS1, CD27, and CD70 deficiencies in humans have revealed key factors of T‐lymphocyte expansion, a critical prerequisite for an efficient immunity to Epstein–Barr virus (EBV) infection. RASGRP1 is a T‐lymphocyte‐specific nucleotide exchange factor known to activate the pathway of MAP kinases (MAPK). A deleterious homozygous mutation in RASGRP1 leading to the loss RASGRP1 expression was identified in two siblings who both developed a persistent EBV infection leading to Hodgkin lymphoma. RASGRP1‐deficient T cells exhibited defective MAPK activation and impaired proliferation that was restored by expression of wild‐type RASGRP1. Similar defects were observed in T cells from healthy individuals when RASGRP1 was downregulated. RASGRP1‐deficient T cells also exhibited decreased CD27‐dependent proliferation toward CD70‐expressing EBV‐transformed B cells, a crucial pathway required for expansion of antigen‐specific T cells during anti‐EBV immunity. Furthermore, RASGRP1‐deficient T cells failed to upregulate CTPS1, an important enzyme involved in DNA synthesis. These results show that RASGRP1 deficiency leads to susceptibility to EBV infection and demonstrate the key role of RASGRP1 at the crossroad of pathways required for the expansion of activated T lymphocytes. Synopsis: RASGRP1 deficiency is characterized by a high susceptibility to develop Epstein‐Barr virus (EBV)‐driven B‐cell lymphoproliferative disorders such as B‐cell lymphoma like Hodgkin lymphoma. This is caused by defective expansion of activated T cells required for an efficient immune response to EBV. RASGRP1 is a critical factor of T‐cell proliferation including CD27‐, CD70‐ and CTPS1‐dependent pathways. RASGRP1 is required for expression of genes involved cell proliferation. This study emphasizes that T‐cell expansion is a critical step in immunity to EBV. Abstract : RASGRP1 deficiency is characterized by a high susceptibility to develop Epstein‐Barr virus (EBV)‐driven B‐cell lymphoproliferative disorders such as B‐cell lymphoma like Hodgkin lymphoma. This is caused by defective expansion of activated T cells required for an efficient immune response to EBV.